Corporate Governance as Part of the Strategic Process: Rethinking the Role of the Board - Weitzner, David; Peridis, Theo (2011)
Managers are most likely to turn to the board of directors for guidance during a period of crisis. But can good corporate governance prevent an organization from reaching that critical point in the first place? In light of the recent global financial crisis, this question has become all the more pressing, and so to prevent future crises, we argue that corporate boards of directors need to be keenly aware of the potential social harms that might arise from the value-creating activities of the firm they are tasked with monitoring. Boards of directors must be vigilant in understanding the firm’s value proposition, perceiving the potential harms that managers tend to overlook, and inserting themselves into the strategy-making process. We offer a typology of scenarios involving potential social harm and benefit and analyze when boards of directors must take a more active role in shaping firm strategy despite resistance from management.
Keywords: Value creation; ethical decision-making; Strategic control; Corporate Governance